Women infected with parasite Toxoplasma have more sons - Kaňková, Šárka; Šulc, Jan; Nouzová, Kamila; Fajfrlík, Karel; Frynta, Daniel; Flegr, Jaroslav (Naturwissenschaften, 2007)
The boy-to-girl ratio at birth (secondary sex ratio) is around 0.51 in most populations. The sex ratio varies between societies and may be influenced by many factors, such as stress and immunosuppression, age, primiparity, the sex of the preceding siblings and the socioeconomic status of the parents. As parasite infection affects many immunological and physiological parameters of the host, we analyzed the effect of latent toxoplasmosis on sex ratios in humans. Clinical records of 1,803 infants born from 1996 to 2004 contained information regarding the mother's age, concentration of anti-Toxoplasma antibodies, previous deliveries and abortions and the sex of the newborn. The results of our retrospective cohort study suggest that the presence of one of the most common parasites (with a worldwide prevalence from 20 to 80%), Toxoplasma gondii, can influence the secondary sex ratio in humans. Depending on the antibody concentration, the probability of the birth of a boy can increase up to a value of 0.72, C.I.95 = (0.636, 0.805), which means that for every 260 boys born, 100 girls are born to women with the highest concentration of anti-Toxoplasma antibodies. The toxoplasmosis associated with immunosuppression or immunomodulation might be responsible for the enhanced survival of male embryos. In light of the high prevalence of latent toxoplasmosis in most countries, the impact of toxoplasmosis on the human population might be considerable.
Keywords: Female; Animals; poměr pohlaví; mužské pohlaví; Financing, Organized; Sex Ratio; protilátky protozoální; Humans; toxoplazmóza; těhotenství; lidé; Toxoplasma; zvířata; Antibodies, Protozoan; ženské pohlaví; Pregnancy; financování organizované; Toxoplasmosis; Male